Aerosol prime-boost vaccination provides strong protection in outbred rabbits against virulent type A Francisella tularensis. - Katherine J O'Malley; Jennifer D Bowling; Elizabeth Stinson; Kelly S Cole; Barbara J Mann; Prachi Namjoshi; Karsten R O Hazlett; Eileen M Barry; Douglas S Reed (PLoS ONE, 2018)
Tularemia, also known as rabbit fever, is a severe zoonotic disease in humans caused by the gram-negative bacterium Francisella tularensis (Ft). While there have been a number of attempts to develop a vaccine for Ft, few candidates have advanced beyond experiments in inbred mice. We report here that a prime-boost strategy with aerosol delivery of recombinant live attenuated candidate Ft S4ΔaroD offers significant protection (83% survival) in an outbred animal model, New Zealand White rabbits, against aerosol challenge with 248 cfu (11 LD50) of virulent type A Ft SCHU S4. Surviving rabbits given two doses of the attenuated strains by aerosol did not exhibit substantial post-challenge fevers, changes in erythrocyte sedimentation rate or in complete blood counts. At a higher challenge dose (3,186 cfu; 139 LD50), protection was still good with 66% of S4ΔaroD-vaccinated rabbits surviving while 50% of S4ΔguaBA vaccinated rabbits also survived challenge. Pre-challenge plasma IgG titers against Ft SCHU S4 corresponded with survival time after challenge. Western blot analysis found that plasma antibody shifted from predominantly targeting Ft O-antigen after the prime vaccination to other antigens after the boost. These results demonstrate the superior protection conferred by a live attenuated derivative of virulent F. tularensis, particularly when given in an aerosol prime-boost regimen.